Optimized silk fibroin piezoresistive nanocomposites for pressure sensing applications based on natural polymers. Issue 6 (29th April 2019) - Reizabal, Ander; Gonçalves, Sérgio; Brito-Pereira, Ricardo; Costa, Pedro; Costa, Carlos M.; Pérez-Álvarez, Leyre; Vilas-Vilela, Jose Luis; Lanceros-Méndez, Senentxu
Abstract : Environmental issues promote the development of sensors based on natural polymers which are becoming an area of increasing interest. Abstract : Environmental issues promote the development of sensors based on natural polymers which are becoming an area of increasing interest. Piezoresistive sensors based on silk fibroin with carbon nanotubes (CNTs) as fillers were produced by solvent-casting in order to tune their electrical conductivity and electromechanical responses. It is shown that the carbonaceous fillers are well dispersed in the polymer matrix and the thermal and mechanical properties are independent of the CNT content. On the other hand, the inclusion of CNTs reduces the β-sheet content of silk fibroin and the electrical properties of the composite strongly depend on the filler content, the percolation threshold being around 1 wt% CNTs. The piezoresistive response demonstrates good reproducibility during cyclic loading without hysteresis with a piezoresistive sensitivity of ∼4 MPa −1, regardless of the CNT content. Overall, the results confirm that polymer composites based on natural polymers exhibit excellent piezoresistive responses, also demonstrated by the implementation and testing of a pressure sensor with the corresponding readout electronics. Thus, it is shown that natural polymers such as silk fibroin will allow the development of a new generation of multifunctional force and deformation sensors.